Public Private Partnership in Greenfield Airports Model Concession Agreement May 2009 - Planning Commission (Planning Commission, 2009)
The Eleventh Five Year Plan envisages that about 30 per cent of the investment in infrastructure would be mobilised from the private sector, as compared to 20 per cent during the Tenth Plan. In order to promote private investment in a fair, transparent and competitive manner, one of the key priorities has been to evolve and standardise the policy and contractual framework for undertaking infrastructure projects through well-structured Public-Private Partnerships (PPPs). Among the infrastructure sectors, civil aviation has been one of the fastest growing in India. Over the recent years, it has become a means of transport for the common man.
Planning Commission Government of India
Planning Commission Government of India